Effect and possible mechanisms of saponins in Chinese herbal medicine exerts for the treatment of myocardial ischemia-reperfusion injury in experimental animal: a systematic review and meta-analysis - Sun, Jiahao; Fan, Jiarong; Yang, Fan; Su, Xin; Li, Xinye; Tian, Li; Liu, Can; Xing, Yanwei (Frontiers in Cardiovascular Medicine, 2023)
Introduction Preventing ischemia-reperfusion injury is the main direction of myocardial infarction treatment in the convalescent stage. Some studies have suggested that saponins in Traditional Chinese medicine (TCM) preparations can protect the myocardium by various mechanisms. Our meta-analysis aims to evaluate the efficacy of TCM saponins in treating myocardial ischemia-reperfusion injury (MIRI) and to summarize the potential molecular mechanisms further. Methods We conducted a literature search in six electronic databases [Web of Science, PubMed, Embase, Cochrane Library, Sinomed, China National Knowledge Infrastructure (CNKI)] until October 2022. Results Seventeen eligible studies included 386 animals (254 received saponins and 132 received vehicles). The random effect model is used to calculate the combined effect. The effect size is expressed as the weighted average difference (WMD) and 95% confidence interval (CI). Compared with placebo, saponins preconditioning reduced infarct size after MIRI significantly (WMD: −3.60,95% CI: −4.45 to −2.74, P < 0.01, I2: 84.7%, P < 0.001), and significantly increased EF (WMD: 3.119, 95% CI: 2.165 to 4.082, P < 0.01, I2: 82.9%, P < 0.0 L) and FS (WMD: 3.157, 95% CI: 2.218 to 4.097, P < 0.001, I2: 81.3%, P < 0.001). Discussion The results show that the pre-administration of saponins from TCM has a significant protective effect on MIRI in preclinical studies, which provides an application prospect for developing anti-MIRI drugs with high efficiency and low toxicity.